1997
DOI: 10.1111/j.1432-1033.1997.t01-2-00625.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Potential Antagonists of Human Interleukin 5 Demonstrates Their Cross‐Reactivity with Receptors for Interleukin 3 and Granulocyte‐Macrophage Colony‐Stimulating Factor

Abstract: The ligand-binding a-chain of the human interleukin 5 (IL-5) receptor was expressed in its soluble form, lacking the transmembrane and cytoplasmic domains, from recombinant baculovirus. The soluble receptor was used in a scintillation proximity assay to identify two chemical compounds that inhibit binding of human IL-5 to the soluble receptor a chain with IC,, of 8 pM and 11 pM, These compounds also inhibited the interaction of human IL-5 with its membrane-bound receptor, composed of the ligandbinding a chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…We obtained similar results for all samples, showing a molecular mass of 42 kDa (Figure 4). This is consistent with published results [5,48].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…We obtained similar results for all samples, showing a molecular mass of 42 kDa (Figure 4). This is consistent with published results [5,48].…”
Section: Resultssupporting
confidence: 94%
“…The expression of shIL‐5Rα has been carried out before in insect cells, with both S2 and Sf9 cells, in shaker flasks. It has been shown that insect cells are capable of producing functional shIL‐5Rα [5,48]. Production in prokaryotic cells is not an option because prokaryotic cells are not able to perform the post‐translational modifications necessary to produce functional shIL‐5Rα, and it has been shown that shIL‐5Rα loses activity when deglycosylated [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although this has resulted in the identification of a number of promising molecules [76], some of them have proven to be too toxic for therapeutic applications or have been shown to also block IL-3 and GM-CSF mediated effects, again eliminating them as potential therapeutic agents [77,78]. These various points illustrate the difficulty in properly antagonizing IL-5 receptor activation.…”
Section: Il-5 Antagonismmentioning
confidence: 99%
“…Several low molecular mass compounds which interfere with the binding of IL-5 to IL-5R have been reported [24,25]. However, they are neither potent nor selective enough to suppress IL-5 activity in vitro.…”
Section: Introductionmentioning
confidence: 98%